Analisis Pendapatan Usahatani Jagung Di Desa Pinaesaan Kecamatan Tompasobaru Kabupaten Minahasa Selatan - Sumaraw, Virginia; Benu, Olfie Liesje Suzana; Rengkung, Leonardus Ricky (Sam Ratulangi University, 2023)
This study aims to analyze the costs used in corn farming and to describe the income received by corn farmers in Pinaesaan Village, Tompasobaru District, South Minahasa Regency. This research was carried out in October 2021. The method used in data collection was the observation method which was carried out during the research until the final report by observing the production process to marketing. The data used are primary data obtained through questionnaires and direct interviews with farmers, then secondary data is obtained from the local Village Government Office. The research variables analyzed were costs, production, revenues, and income. The results showed that the average total cost incurred by corn farmers was IDR5.055.471/Ha and with revenues of IDR8.427.672/Ha so that they could produce an average income of IDR3.371.949/Ha.